Morphology Characterization, Molecular Phylogeny, and Pathogenicity of Diaporthe passifloricola on Citrus reticulata cv. Nanfengmiju in Jiangxi Province, China - Chingchai Chaisiri; Xiang-Yu Liu; Wei-Xiao Yin; Chao-Xi Luo; Yang Lin (Plants, 2021)
The Nanfengmiju (Citrus reticulata cv. Nanfengmiju), a high-quality local variety of mandarin, is one of the major fruit crops in Jiangxi Province, China. Citrus melanose and stem-end rot, two common fungal diseases of Nanfengmiju, are both caused by Diaporthe spp. (syn. Phomopsis spp.). Identification of the Diaporthe species is essential for epidemiological studies, quarantine measures, and management of diseases caused by these fungi. Melanose disease was observed on Nanfengmiju fruit in Jiangxi Province of China in 2016. Based on morphological characterization and multi-locus phylogenetic analyses, three out of 39 isolates from diseased samples were identified as D. passifloricola. Since these three isolates did not cause melanose on citrus fruit in the pathogenicity tests, they were presumed to be endophytic fungi present in the diseased tissues. However, our results indicate that D. passifloricola may persist as a symptom-less endophyte in the peel of citrus fruit, yet it may cause stem-end if it invades the stem end during fruit storage. To the best of our knowledge, this is the first report of D. passifloricola as the causal agent of the stem-end rot disease in Citrusreticulata cv. Nanfengmiju.